Elastohydrodynamics lubrication for bio-based lubricants in elliptical conjunction - Zakaria, Nazri Huzaimi (2010)
The issue of elastohydrodynamic lubricants in industry has been investigated by many researchers. Whereby many machine elements, such as gear teeth, cams and followers and rolling-element bearings are working under spinning and rolling conditions. Thus, the function of lubricant is to prevent friction and wear which causes material failure between two surfaces. Bio-based lubricants are one of the possibilities that might be used as a substitute to the conventional lubricants in the industries. Therefore, in this research we focused on elastohydrodynamic lubrication flows at the elliptical conjunctions by using bio-based lubricants. The numerical approach is used in this study to determine the effect of elliptical conjunctions by using the Gambit and Fluent software. This software helps to verify the deformation of the pressure distribution at the conjunctions. We had obtained that at constant speed, the mineral oil has the highest value of dynamics pressure than bio-based lubricants along X and Y axis between two surfaces. So, the mineral oil will able to carry more load than bio-based lubricant. However, we obtain that the bio-based lubricant is the best lubricant to protect the surfaces from wear and damage than mineral oil because mineral oil has higher value of dynamics pressure than bio-based lubricant.